2011
DOI: 10.1007/s11192-011-0416-8
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of research in China assessed with Essential Science Indicators

Abstract: To provide an overview of the characteristics of research in China, a bibliometric evaluation of highly cited papers with high-level representation was conducted during the period from 1999 to 2009 based on the Essential Science Indicators (ESI) database. A comprehensive assessment covered overall performance, journals, subject categories, internationally collaborative countries, national inter-institutionally collaborative institutions, and most-cited papers in 22 scientific fields. China saw a strong growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
38
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 48 publications
7
38
1
2
Order By: Relevance
“…Aksnes's (2003) study of 297 Norway's highly cited papers identified typical characteristics such as they are authored by a large number of scientists and involve extensive international collaboration as quality dynamics. Similar studies conducted in China (Fu et al 2011), Taiwan (Miyairi and Chang 2012) and Russia (Pislyakov and Shukshina 2014) substantiate the widely accepted view that international collaboration is almost a requirement for publishing highly cited papers. About 47 percent of all China ESI papers have collaboration with the group of eight (G8) highly industrialized nations, especially the United States (Fu et al 2011).…”
Section: Introductionsupporting
confidence: 75%
See 3 more Smart Citations
“…Aksnes's (2003) study of 297 Norway's highly cited papers identified typical characteristics such as they are authored by a large number of scientists and involve extensive international collaboration as quality dynamics. Similar studies conducted in China (Fu et al 2011), Taiwan (Miyairi and Chang 2012) and Russia (Pislyakov and Shukshina 2014) substantiate the widely accepted view that international collaboration is almost a requirement for publishing highly cited papers. About 47 percent of all China ESI papers have collaboration with the group of eight (G8) highly industrialized nations, especially the United States (Fu et al 2011).…”
Section: Introductionsupporting
confidence: 75%
“…Similar studies conducted in China (Fu et al 2011), Taiwan (Miyairi and Chang 2012) and Russia (Pislyakov and Shukshina 2014) substantiate the widely accepted view that international collaboration is almost a requirement for publishing highly cited papers. About 47 percent of all China ESI papers have collaboration with the group of eight (G8) highly industrialized nations, especially the United States (Fu et al 2011). Taiwan's international collaboration in its production of highly cited papers remain relatively stable with USA with the highest number of collaboration, followed by China, Japan and Germany.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…The most productive institution -RAS had an overwhelming majority in the total articles, and CAS was just down by three articles in 2010, following distantly by the other institutions. CAS as the China's highest academic institution in natural sciences played an active role in terms of scientific outputs in recent years as the exponentially growth scientific production in China (Li et al, 2009;Fu et al, 2010;Tanaka &Ho, 2011;Fu et al, 2011;Li et al, 2011). Although three universities in China including Central South University, Naval University of Engineering, and SiChuan University just ranked 10 th , 39 th , and 43 rd of total articles from 1991 to 2010, but they had high rankings (3 rd , 4 th , and 7 th ) with respect to the number of articles in 2010.…”
Section: Comparison Of Top Seven Institutionsmentioning
confidence: 99%